CLINICAL CHARACTERISTICS OF RESPIRATORY INVOLVEMENT IN CHILDREN WITH CYSTIC FIBROSIS IN THE CHUVASH REPUBLIC - O. I. Golubtsova; S. A. Krasovskiy; S. L. Kozhevnikova; N. I. Kapranov ("Paediatrician" Publishers LLC, 2012)
Cystic fibrosis is a common hereditary disease, characterized by multiple organ dysfunction, including early and severe involvement of respiratory system. The disease is caused by CFTR (cystic fibrosis transmembrane conductance regulator) gene mutation. Respiratory tract involvement is a main factor, predicting outcome, mortality, life quality and morbidity of patients. Genetic examination of Chuvash children demonstrated, that 53,5% of patients' chromosomes are carriers of E92K mutation. According to genetic epidemiology of cystic fibrosis, Chuvash ethnic group is unique, as the prevalence of mutation E92K in it is almost twice higher than the most common and «severe» mutation in the world - F508del. The significant predominance of E92K determined the clinical presentation of cystic fibrosis in the examined group, because this mutation refers as «mild». The critical moment in treatment of this disorder is influence on sputum viscosity. Dornase alpha proved itself as an effective drug, which advantages among other agents, improving sputum rheological properties, are caused not only by unique mucolytic effect, but also anti-inflammatory and antibacterial actions.